Kienbock Disease - Sajad Ahmad Salati; Sari M Rabah (Online Journal of Health & Allied Sciences, 2010)
A case of a 27 years old female with history of pain in left wrists is presented. Investigations revealed necrosis of left lunate (Kienbock disease).